EXCHANDE OF PROTEINCARBOHYDRATE COMPLEXES IN SERUM BLOOD AND SYNOVIAL FLUID UNDER DIFFERENT METHODS OF TREATMENT ASEPTIC ARTHRITIS IN HORSES - Іздепський, В. Й.; Іздепський, А. В. (Scientific Progress & Innovations, 2013)
Results highlight features of exchange of protein containing compounds in serum and synovial fluid at various treatments of aseptic arthritis in horses. In comparative aspect the efficacy of intraarticular injections of various medicinal compounds containing anesthetic and antiinflammatory components is studied. It was found that the use of Movalis in combination with trifuzolom promotes rapid exchange recovery seromucoid sialic acids in serum and synovial fluid in comparison with diprospanom.